Characterization of microbiota composition and presence of selected antibiotic resistance genes in carriage water of ornamental fish - Gerzova, Lenka; Videnska, Petra; Faldynova, Marcela; Sedlar, Karel; Provaznik, Ivo; Cizek, Alois; Rychlik, Ivan (PloS one, 2014)
International trade with ornamental fish is gradually recognized as an important source of a wide range of different antibiotic resistant bacteria. In this study we therefore characterized the prevalence of selected antibiotic resistance genes in the microbiota found in the carriage water of ornamental fish originating from 3 different continents. Real-time PCR quantification showed that the sul1 gene was present in 11 out of 100 bacteria. tet(A) was present in 6 out of 100 bacteria and strA, tet(G), sul2 and aadA were present in 1-2 copies per 100 bacteria. Class I integrons were quite common in carriage water microbiota, however, pyrosequencing showed that only 12 different antibiotic gene cassettes were present in class I integrons. The microbiota characterized by pyrosequencing of the V3/V4 variable region of 16S rRNA genes consisted of Proteobacteria (48%), Bacteroidetes (29.5%), Firmicutes (17.8%), Actinobacteria (2.1%) and Fusobacteria (1.6%). Correlation analysis between antibiotic resistance gene prevalence and microbiota composition verified by bacterial culture showed that major reservoirs of sul1 sul2, tet(A), tet(B) tet(G), cat, cml, bla, strA, aacA, aph and aadA could be found among Alpha-, Beta- and Gammaproteobacteria with representatives of Enterobacteriaceae, Pseudomonadaceae, Rhizobiaceae and Comamonadaceae being those most positively associated with the tested antibiotic resistance genes.
Keywords: Animals; Proteobacteria; integrony; RNA, Ribosomal, 16S; RNA ribozomální 16S; Bacteroidetes; Anti-Bacterial Agents; Fishes; Microbiota; ryby; Fusobacteria; mikrobiota; Bacteria; mnohočetná bakteriální léková rezistence; Drug Resistance, Multiple, Bacterial; Actinobacteria; Water Microbiology; zvířata; mikrobiologie vody; Integrons; antibakteriální látky; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction